Effectiveness of screening colonoscopy in reducing the risk of death from right and left colon cancer: a large community-based study - Doubeni, Chyke A; Corley, Douglas A; Quinn, Virginia P; Jensen, Christopher D; Zauber, Ann G; Goodman, Michael; Johnson, Jill R; Mehta, Shivan J; Becerra, Tracy A; Zhao, Wei K; Schottinger, Joanne; Doria-Rose, V Paul; et al. (Gut, 2018)
ObjectiveScreening colonoscopy's effectiveness in reducing colorectal cancer mortality risk in community populations is unclear, particularly for right-colon cancers, leading to recommendations against its use for screening in some countries. This study aimed to determine whether, among average-risk people, receipt of screening colonoscopy reduces the risk of dying from both right-colon and left-colon/rectal cancers.DesignWe conducted a nested case–control study with incidence-density matching in screening-eligible Kaiser Permanente members. Patients who were 55–90 years old on their colorectal cancer death date during 2006–2012 were matched on diagnosis (reference) date to controls on age, sex, health plan enrolment duration and geographical region. We excluded patients at increased colorectal cancer risk, or with prior colorectal cancer diagnosis or colectomy. The association between screening colonoscopy receipt in the 10-year period before the reference date and colorectal cancer death risk was evaluated while accounting for other screening exposures.ResultsWe analysed 1747 patients who died from colorectal cancer and 3460 colorectal cancer-free controls. Compared with no endoscopic screening, receipt of a screening colonoscopy was associated with a 67% reduction in the risk of death from any colorectal cancer (adjusted OR (aOR)=0.33, 95% CI 0.21 to 0.52). By cancer location, screening colonoscopy was associated with a 65% reduction in risk of death for right-colon cancers (aOR=0.35, CI 0.18 to 0.65) and a 75% reduction for left-colon/rectal cancers (aOR=0.25, CI 0.12 to 0.53).ConclusionsScreening colonoscopy was associated with a substantial and comparably decreased mortality risk for both right-sided and left-sided cancers within a large community-based population.